Čas v modení a postmodení literatuře, zejména dramatické - Hoffmann, Bohuslav (Stylistyka, 2021)
The author of the article tries to connect opinions on time of some modem and post-modem philosophers and sociologists of the 19th and 20th centuries (Hegel, Marx, Bergson, Foucault, Baudrillard, Bauman, Deleuze, Bćlohradsky, Mizińska...) with some texts of Czech and world, modem and postmodem literaturę (particularly with drama) of the same time: A. and V. Mrstikove - Rok na vsi; K. Toman - Mćsice; M. Proust - A la re- cherche du temps perdu; S. Beckett - En attendant Godot, Fin de partie, Krapp’s Last Tape, Nouvelles et Textes pour rien; K. Śiktanc - Ćesky orloj; V. Macura - Ten, ktery budę; M. Ravenhill - Shopping and Fucking, Faust (Faust is dead); S. Kane - 4.48 Psy- chosis; M. HoroSćak-Vafenyhlavy aneb „Dćvće, tobS na kozach tanći smrt“; W. Mastrosimone - Like Totally Weird. It is obvious that time is incorporated in the titles of most of these works.